2021
DOI: 10.47391/jpma.03-494
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of low back pain in young adults and its relationship with different mattresses

Abstract: Objective: The purpose of this study was to find out the frequency of low back pain in young adults and its relationship with the mattresses they use.Methodology: This cross sectional study was carried out in 6 months in twin cities (Rawalpindi and Islamabad). The sample size for this study was 366. For data collection, self-structured questionnaire was used along with Modified Oswestry Scale and Numeric Pain Rating Scale (NPRS). The inclusion criteria for this study was young adults with age limit 18-35 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…This finding is further supported by another Malaysian study identifying a poor-quality mattress as a crucial factor in LBP incidence [29]. A study conducted in Pakistan confirmed our research findings, emphasizing that individuals who have used a mattress for more than three years are more prone to experience LBP [12].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This finding is further supported by another Malaysian study identifying a poor-quality mattress as a crucial factor in LBP incidence [29]. A study conducted in Pakistan confirmed our research findings, emphasizing that individuals who have used a mattress for more than three years are more prone to experience LBP [12].…”
Section: Discussionsupporting
confidence: 88%
“…However, these findings cannot be generalized, as individual needs can significantly influence the optimal mattress choice for LBP management [23]. Moreover, several studies have highlighted the significance of pillow care and mattress firmness combined with body posture, sleep comfort, and LBP development [12,24]. This aspect, however, represents a limitation of our study, as it did not consider pillow use-an essential factor for future research to explore.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Mechanical back pain accounts for 97% of cases, arising from spinal structures such as bone, ligaments, discs, joints, nerves, and meninges. Acute back pain in the absence of progressive neurologic deficits and other underlying non-mechanical causes may be treated conservatively, with specific emphasis on maintaining activity levels and function (Muazzam et al, 2021). Retro-walking also known as backward walking to help people improve walking pattern called as gait and mobility in the lower extremities.…”
Section: Introductionmentioning
confidence: 99%